Aristolochia rethyae, a new species from Arunachal Pradesh, north-east India - Kashung, Soyala; Gajurel, Padma Raj; Singh, Binay; Barman, Rimi; Yakang, Tage (Phytotaxa, 2022)
Aristolochia rethyae, a new species from Arunachal Pradesh, north-east India, is described. Aristolochia rethyae is affinis to A. griffithii and A. tanzawana with similar leaf texture and shallowly 3-lobed perianth limb, but differs from A. griffithii in its ovate to narrowly ovate leaf shape, cauliflorous flower borne in a cluster and densely hirsute brown capsule, and from A. tanzawana in their cauliflorous inflorescence, S-shaped perianth and capsule size with distinct wavy ridges.